Submaximal running economy in run-trained pre-pubertal boys - Unnithan, V. B.; Timmons, J. A.; Brogan, R. T.; Paton, J. Y.; Rowland, T. W. (The Journal of Sports Medicine and Physical Fitness, 1996)
There is an increasing tendency for young children to participate in training and competitive running. The impact long-term training has upon stimulating functional physiological adaptation has yet to be fully understood. In this study cardio-respiratory and kinematic differences were assessed at submaximal and maximal exercise intensities in run-trained and non-run-trained boys. Thirty three pre-pubertal boys volunteered to take part in the study. The subjects were in two groups: 15 run-trained subjects [age 11.7 +/- 1.06 yrs, mean +/- SD] and 18 non-run-trained (control) subjects [age 11.3 +/- 0.90 yrs]. Two separate (4 x 3 min) submaximal protocols were used for the trained and non-run-trained groups, with two of the speeds overlapping for comparison purposes. In addition, all boys also performed a maximal oxygen consumption test. Mean VO2max value for the run trained group was 60.5 +/- 3.3 ml/kg/min and for the control group 51.1 +/- 4.3 ml/kg/min, (p < 0.001). No significant differences were found for submaximal running economy at either comparison speed. In addition, no significant (p > 0.05) differences were noted between the groups for any of the kinematic variables at the two comparison speeds. However, selected physiological differences did exist at the submaximal running speeds. The source of the differences that did exist between the two groups may be the result of training, genetic pre-selection or developmental differences between the groups.